Content of elements in wheat grain cultivated with beneficial microorganisms applied - Zamana Svetlana; Kondratyeva Tatiana; Rubanov Alexey (BIO Web of Conferences)
The study aimed to determine the influence of beneficial bacteria and fungi on the level of 40 chemical elements in winter wheat grain. Element content of wheat grain cultivated in the field trial was analyzed using an inductively coupled plasma atomic emission spectrometer Optima 2000 DV and an inductively coupled plasma mass spectrometer Elan 9000 (both manufactured by Perkin Elmer, USA). The application of beneficial bacteria (Bacillus subtilis, Bacillus megaterium, Azotobacter chroococcum), antagonistic fungi (Trichoderma viride, Trichoderma harzianum), and arbuscular mycorrhizal fungi (Glomus interradices) during wheat cultivation led to an increase in levels of most of the analyzed chemical elements in the grain (Ag, Al, Au, B, Ba, Be, Bi, Ca, Co, Cr, Cu, Fe, Ga, Ge, I, K, La, Li, Mg, Mo, Na, Ni, Pb, Pt, Sb, Se, Si, Sn, Sr, Tl, V, W, and Zn), except for phosphorus, manganese, arsenic, cadmium, mercury, rubidium, and zirconium.